Republic of Armenia : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Modification of Performance Criteria; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Armenia. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Fifth Review Under the Poverty Reduction and Growth Facility (PRGF) for Armenia. Fiscal policy has been prudent, but increasing expenditure pressures are creating medium-term fiscal risks. Tax collection still falls short of financing needs for infrastructure and poverty-reducing services, calling for further strengthening of tax administration. Monetary policy will need to be tightened in light of rising inflation risks. A firm commitment to a medium-term inflation target will be critical for anchoring price expectations and building credibility in the transition to full-fledged inflation targeting.